Efficacy of using non-linear pedagogy to support attacking players` individual learning objectives in elite-youth football: A randomised cross-over trial - Roberts, S. J.; Rudd, J. R.; Reeves, M. R. (Journal of Sports Sciences, 2020)
The present study examined the efficacy of a coaching curriculum, based on non-linear pedagogy, on improving attacking players` individual learning objectives (ILOs) in elite-youth football. Participants included 22 attacking players (i.e., centre-forwards, wide-players and attacking midfield players) from a professional football academy in England. The players were randomly appointed to both control (CON) and intervention (INT) periods following baseline measures. The INT (non-linear) and CON (linear) periods were both designed to support the ILOs provided to each player as part of the elite player performance plan. The study adopted a randomised cross-over design and ILOs considered important for attacking players (i.e., strong foot finishing, weak foot finishing, 1-v-1 and decision-making) were evaluated using the Loughborough Shooting Skill Test. The results showed significant differences for INT in 1-v-1 (P< 0.02) and decision-making (P< 0.01). However, there were no significant differences for strong foot finishing, weak foot finishing or time taken. These results support non-linear pedagogy in developing 1-v-1 game play and decision-making but not for technical shooting proficiency.